HERITAGE TOURISM REVITALIZATION AND URBAN AIR QUALITY: ASSESSING ENVIRONMENTAL TRADE-OFFS IN URBAN DISTRICTS - Wibowo, Andri (Jurnal Pensil : Pendidikan Teknik Sipil, 2026)
Urban heritage revitalization has increasingly been adopted as a strategy to stimulate economic growth and enhance city attractiveness through tourism development. However, such functional transformations may also generate environmental pressures, particularly on urban air quality, creating potential trade-offs between economic benefits and environmental sustainability. This study aims to assess the impact of heritage tourism revitalization on air pollutant concentrations and to identify the key factors contributing to air quality degradation in urban districts. A mixed-methods case study was conducted through indoor–outdoor air quality measurements, field observations, interviews, and documentation in the Kayutangan heritage corridor, Malang City, Indonesia, serving as an empirical setting. Data were analyzed using the Miles–Huberman model and Greenship Existing Building version 1.1 parameters focusing on Indoor Health and Comfort. The results indicate that increased traffic density, tourist activity, and commercial operations significantly elevated CO₂, TVOC, and formaldehyde concentrations, with several measurements exceeding recommended health standards. These findings demonstrate the environmental trade-offs associated with heritage tourism revitalization and highlight the need for integrated transportation management, emission control, and continuous air quality monitoring to ensure sustainable urban development.